UJI TOKSISITAS DAN AKTIVITAS ANTIBAKTERI BERBAGAI FRAKSI EKSTRAK DAUN TANAMAN KAMBOJA (Plumeria acuminate Ait.) - Subur P Pasaribu; Wahidatul Nuriah; Erwin - (JURNAL KIMIA MULAWARMAN, 2013)
Research about phytochemical, brine shrimp lethality and antibacterial activity tests in each fraction from kamboja leaves (Plumeria acuminate Ait.) from Loa Janan, East Kalimantan has been carried out. Plumeria acuminate Ait. leaves was extracted with ethanol and then concentrated by using rotary evaporator. The total extract was fractioned with n-hexane, and ethyl acetate. Based on the secondary metabolites phytochemical test of the Plumeria acuminate Ait. leaves show that total extract is contain alkaloid, steroid, and phenolic. n-hexane fraction is contain steroid. Ethyl acetate fraction is contain steroid. Ethanol-water fraction is contain alkaloid and phenolic. Brine shrimp lethality test exhibit mortality rate of Artemia salina (L) by Probit SAS analysis to determine lethal concentration 50% (LC 50 ) value. The test show that the most active was ethyl acetate fraction with LC 50 value of 44.7968 ppm. Antibacteria activity test of extracts for Staphylococcus aureus bacteria (positive Gram) and Escherichia coli (negative Gram) was carried out by paper disc method. The test showed that the most active were ethyl acetate fraction with minimum inhibitor consentration of 1.563% which clear zone diameter was 5.3 mm on Staphylococcus aureus bacteria and 6.3 mm on Escherichia coli bacteria.